Emerging risk in international banking : origins of financial vulnerability in the 1980s - Snowden, P. N. (P. Nicholas) (London : Routledge, 2012)
Contributes to the historical perspective on modern diagnoses of policy weakness and financial sector excess .
Repr. of ed. published: London : Allen & Unwin, 1985.
Includes bibliographical references and index.
oif 08/09/14
Loan
Keywords: Banks and banking, International; Capital movements; Debts, Public; Bank liabilities